Papel dos probióticos nos sintomas gastrintestinais e no sistema imunológico em pacientes com esclerose sistêmica: um ensaio clínico randomizado, duplo-cego e placebo controlado - Marighela, Thais Fernandes [UNIFESP] (2018)
Introduction: Systemic sclerosis (SSc) is a rheumatic autoimmune disease that particularly affects the gastrointestinal tract (GIT), lung, heart and kidneys. Changes in the balance of Th1/Th2 T cells and between T cell regulatory (Treg) and Th17 levels, as well as changes in the intestinal microbiota may stimulate the inflammatory response and also may lead to damage to the intestinal epithelium. Oral use of probiotics, either to modulate the microbiome or the immune response, may be an attractive option especially in autoimmune diseases. Objectives: To evaluate the efficacy of probiotics on the symptoms of GIT and immune response by evaluating Treg cell levels and Th1, Th2 and Th17 helper T cell levels in SSc patients. Patients and methods: This was a randomized, placebocontrolled, doubleblind clinical trial with 73 patients with SSc randomized to receive a daily dose of probiotics or placebo for 8 weeks. The primary endpoint was changes in GIT symptoms between the baseline and week 8. Clinical evaluation, the University of California at Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract 2.0 (UCLA SCTC GIT 2.0) questionnaire, the Health Assessment Questionnaire Disability Index (HAQDI), the scleroderma health assessment questionnaire (SHAQ) score for GIT symptoms, anthropometric measurements, dietary intake and laboratory evaluation were performed at baseline (T0) and at weeks 4 (T1) and 8 (T2). The proportion of the Th1 (CD3+CD8IFNγ+), Th2 (CD3+CD8IL4+), Th17 (CD3+CD8IL17+) subpopulations and Treg cells were evaluated by the flow cytometry method. RESULTS: Among the 73 SSc patients, 37 were randomized to receive probiotic (mean age 46.7 ± 13.1 years) and 36 received placebo (mean age 46.1 ± 11.9 years). After 8 weeks, there was a significant decrease in the GIT symptoms assessed by the UCLA GIT 2.0 questionnaire in the two groups evaluated, but without significant difference in the comparison between the probiotic and placebo groups (p=0.846). After 8 weeks, there was a significant decrease in the proportion of CD3+CD8IL17+ cells in the probiotic group compared to the placebo group in week 8 (p=0.003). There was no significant difference in the proportion of Th1 and Treg cells in the probiotic group compared to the placebo group (p=0.364; p=0.421; p=0.898, respectively). No difference was observed in the HAQDI questionnaire, SHAQ, energy, macronutrients and fiber intake between the groups. CONCLUSIONS: In the present study there was no significant changes in the GIT symptoms after 8 weeks of probiotic in patientns with SSc. Nonetheless, we observed that the consumption of probiotics led to a significant reduction in the proportion of Th17 cells compared to the placebo group, suggesting an immunomodulatory effect of probiotics in SSc patients.